Suggestion et médiation : du bovarysme au bouvardisme - Atsushi Yamazaki (Flaubert: Revue Critique et Génétique)
The purpose of this paper is to reveal a certain conception of social psychology in Bouvard et Pécuchet. Flaubert developed this conception based on his study on magnetism and he called it theory of suggestion. I would rename it bouvardism, in order to emphasize the affinity with the famous bovarysm. Jules de Gaultier who invented bovarysm shares the same epistemic context with some authors who inspired Flaubert (Louis Figuier or Alfred Maury). Furthermore, the theory of suggestion is presented as a theory of mediation. In order to assess its significance, we shall examine the relations between the theory of suggestion and the theory of mediation proposed by René Girard.